From formal ethics to an ethics of life: the expansion of the categoric imperative in Jonas - Petrachini, William Cepkauskas (Seven Editora, 2023)
The life of the contemporary subject changes due to the presence of technology. There is no way to go back to the point where there was no interference, since, starting in the industrial revolution, the ability to formulate technological solutions started to guide human behavior. Faced with this scenario that intensifies, humanity finds itself in an intertwined relationship with technology. In this wake, Jonas will propose an ethics that aims to understand these transformations, stressing the importance of humanity not losing sight of what is most essential in it: life. In this sense, Jonas will demonstrate that current ethics is based on that theorized by Kant, which has as its guideline the categorical imperative: “Act in such a way that your action can be universalized.”. Even though Jonas does not disregard the Kantian proposal, the criticism is directed towards its aspect, which does not have the power to produce the necessary behavior for the preservation of life, because it cannot generate in the individual an effective action in the real plane, overcoming pure rationality. Thus, it is important that an ethic can influence the subjects, moving their intellectual and affective capacities to an action that unquestionably preserves life. At this point, life receives a differentiated treatment in Jonas’s ethics, because, in wanting to expand the categorical imperative, it is based on an ontological bias, since the moral law that dictates behavior is no longer sufficient to face technological changes. A step further is needed. In the proposal of Jonas’s imperative, this advance is directed towards the preservation of life: "Act in such a way that the effects of your action are not destructive for the future possibility of such a life". In this way, Jonasian ethics examines the foundations of Kantian ethics, listing points of its insufficiency to embrace new social relations. Jonas intends to develop an ethics that holds the uncontrollable power of technology, which generates negative impacts on society and the environment. This work pretends to identify the points criticized by Jonas in Kant’s ethical formulation and what prevents it from dealing with contemporary technological changes. Finally, the research will demonstrate how the formulation of the idea of the "Heuristic of fear" is an essential tool in Jonas’s ethics, providing his ethical system with the ability to propose to humanity the protection of the natural world and life of modern ethics have to be review in favor of life. DOI: https://doi.org/10.56238/devopinterscie-019